2010
DOI: 10.1136/jnnp.2009.190512
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between motor deficit and primary motor cortex hemispheric activation balance after stroke: longitudinal fMRI study

Abstract: Licence for Publication:The Corresponding Author has the right to grant on behalf of all authors and does grant on behalf of all authors, an exclusive licence (or non exclusive for government employees) on a worldwide basis to the BMJ Publishing Group Ltd to permit this article (if accepted) to be published in PMJ and any other BMJPGL products and sublicences such use and exploit all subsidiary rights, as set out in our licence. 2 AbstractBackground: In the chronic stage of stroke, previous work has shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 21 publications
(40 reference statements)
1
50
0
2
Order By: Relevance
“…Functional recovery after stroke has been observed and is currently attributed to both brain remodeling and plasticity (1)(2)(3)(4). Structural and functional remodeling of areas next to an infarct or remote regions can alter signaling within bilateral neuronal networks and thus contribute to functional recovery (3)(4)(5)(6)(7). Rewiring of neural connections is mediated by electrical activity, which can activate a number of plasticity mechanisms, including the release of activity-dependent neurotrophins such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) (8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional recovery after stroke has been observed and is currently attributed to both brain remodeling and plasticity (1)(2)(3)(4). Structural and functional remodeling of areas next to an infarct or remote regions can alter signaling within bilateral neuronal networks and thus contribute to functional recovery (3)(4)(5)(6)(7). Rewiring of neural connections is mediated by electrical activity, which can activate a number of plasticity mechanisms, including the release of activity-dependent neurotrophins such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) (8)(9)(10).…”
mentioning
confidence: 99%
“…Brain stimulation is a promising area of research because it allows direct activation and manipulation of the target area's excitability (14)(15)(16). The primary motor cortex (M1) is a commonly stimulated area as it directly innervates the corticospinal tract to initiate movement (1,7). Although electrical stimulation and transcranial magnetic stimulation show promise in promoting recovery (17,18), these techniques are limited by imprecision and indiscriminate activation or inhibition of all cell types near the stimulated site; thus, they can produce undesired effects such as psychiatric and motor/speech problems (19)(20)(21).…”
mentioning
confidence: 99%
“…An improvement in radio-uptake, and thus presumably perfusion, of 15% or greater was found in all patients at the time of the second scan. The volume of perihematomal brain in which this improvement was noted ranged from 7.2 to 71.3 cm 3 . This area was felt to represent at least part of the area of perihematomal hypoperfusion and suggests that aggressive measures to maintain perfusion and oxygenation to tissues could improve outcomes.…”
Section: Management and Monitoring Of Ichmentioning
confidence: 95%
“…The DEFUSE-EPITHET trial assessed 111 patients undergoing tPA for stroke using pretreatment DWI and PWI modalities. It was found that 89% of patients with a PWI-detected brain volume of 85 cm 3 with a "Tmax" (time until the theoretical maximal amount of residue function) greater than 8 seconds who achieved reperfusion had a modified Rankin Scale score of 5 or 6 at 90 days. Of these, only 67% were secondary to at least some level of parenchymal hemorrhage, which was also significantly more likely using the 85-cm 3 cutoff.…”
Section: Predicting Hemorrhage After Ischemic Eventsmentioning
confidence: 99%
See 1 more Smart Citation